Problem based learning: tutors’ views 5 years after implementation at a sub-Saharan University - Galukande, Moses; Katamba, Achilles; Kiguli, Sarah; Kiguli-Malwadde, Elsie; Kijjambu, Stephen; Sewankambo, Nelson (African health sciences, 2015)
Curriculum evaluation is key to continuous assurance of quality of education. Objectives: To assess the teachers’ perceptions on how well student teaching and learning activities were conducted at an institution that had practiced PBL for five years. Methods: A cross sectional descriptive study. 150 teachers from 23 departments at the College of Health Sciences participated in the study. A 25 item self-administered questionnaire was used to collect data. Activities evaluated included; students assessment, self-directed learning, feedback and clinical exposure. Data were entered in epi data and analysed using SPSS. Ethical approval was obtained. Results: The participants’ average teaching experience was eight years. The PBL/COBES approach mostly achieved the aim of producing self-directed and lifelong learners. Half of the teaching staff actively provided regular feedback about the learning and teaching activities they were involved in. Early clinical exposure was widely accepted as a highly rewarding appropriate teaching and learning strategy. COBES activities were well organized although involvement of College staff was low. Conclusion: PBL/COBES program was successfully executed and had high acceptance among Faculty. The biggest challenge was getting all staff to provide regular feedback. Self institutional curriculum review can be done cheaply and quickly to provide feedback for continual curriculum improvement.
Keywords: Problem Based Learning; Evaluation; Curriculum; University